2014
DOI: 10.1021/om5008852
|View full text |Cite
|
Sign up to set email alerts
|

Site Selectivity of [RuCp*]+ Complexation in Cyclopenta[def]triphenylenes

Abstract: A series of new cyclopenta-fused triphenylenes has been synthesized in high yield and reacted with [Ru(μ 3 -Cl)Cp*] 4 to form [RuCp*(η 6 -arene)]PF 6 complexes. Systematic variation of the cyclopenta[def ]triphenylene allowed the site of complexation to be probed and the influence of the electronic and steric properties of the substituents in directing complexation to be assessed. As determined by NMR spectroscopy and X-ray crystallography, in all cases the [RuCp*] + fragment complexes at a peripheral arene ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…[18] However,t he in-plane geometricalp arameters in the region adjacent to the cyclopentaring are distorted:a nalysis of 2c shows that the peripheral bondsa re mostly elongated and the internal bonds shortened. Similarly,b ond angles involvingt he benzenoid rings of 2c are also distorted in this region when compared to HBC(tBu) 6 ,b ecomingl ess so toward the centre of the core. Both 10 b and 2c crystallise as offset dimer pairs.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…[18] However,t he in-plane geometricalp arameters in the region adjacent to the cyclopentaring are distorted:a nalysis of 2c shows that the peripheral bondsa re mostly elongated and the internal bonds shortened. Similarly,b ond angles involvingt he benzenoid rings of 2c are also distorted in this region when compared to HBC(tBu) 6 ,b ecomingl ess so toward the centre of the core. Both 10 b and 2c crystallise as offset dimer pairs.…”
mentioning
confidence: 89%
“…Additionally, the benzylic methylene carbon offers a new reactive site, allowing for further modification, such as the formation of cyclopentadienyl‐type ligands able to form metallocenes, of importance as Ziegler–Natta catalysts, or for tuning of the electronic/supramolecular properties, such as the modification of polyfluorenes to yield more photochemically stable polymers . Our group has reported the synthesis of cyclopentatriphenylene, and as an expansion of this, our sights were set on annulation to the larger PAH, hexa‐ peri ‐hexabenzocoronene (HBC), an extensively studied, well‐defined ‘nanographene“ which participates in robust π‐stacking interactions leading to long‐range order as applied in organic electronics . Although a cyclopentadiene bis‐ ortho ‐annulated by two HBCs with the trivial name ”superfluorene“ has been reported, we endeavoured to ”bridge“ a bay region with a methylene group to give a cyclopenta‐HBC (CpHBC, 2 a , Figure ) as a step toward systematically modulating the structure and reactivity of the HBC core.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Regioselectivity plays an important role in many areas of organic chemistry, including synthesizing pharmaceuticals and elucidating their mechanisms of action. In other words, regioselectivity in organic chemistry is important for controlling reactions, improving synthetic efficiency, and advancing fields such as pharmaceuticals and organic electronics. While there are examples of regioselective reactions in inorganic and coordination chemistry, they are less common than in organic chemistry . Conventional regioselective coordination refers to a ligand with multiple binding sites in a molecule, each of which binds a different type of metal ion that prefers a particular site.…”
Section: Introductionmentioning
confidence: 99%
“…While there are examples of regioselective reactions in inorganic and coordination chemistry, they are less common than in organic chemistry. 7 Conventional regioselective coordination refers to a ligand with multiple binding sites in a molecule, each of which binds a different type of metal ion that prefers a particular site. For example, Lehn et al reported that simple molecular systems with heterocyclic ligands exhibit regioselectivity.…”
Section: ■ Introductionmentioning
confidence: 99%